ANALISIS FORWARD CONTRACT HEDGING, MONEY MARKET HEDGING DAN OPEN POSITION DALAM MENGHADAPI EKSPOSUR VALUTA ASING DI MASA COVID-19 - Syarif Alamsyah; Rengga Madya Pranata; Wildan Army Abdillah (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2021)
Multinational companies around the world will always be faced with risks due to international transactions. One of the risks that will be faced by multinational companies is transaction exposure that arises due to currency fluctuations which can affect the company's cash flows in the future and is influenced by the presence of the COVID-19 virus pandemic resulting in economic disruption, especially in Indonesia, one aspect that is significantly disrupted namely, the Indonesian currency exchange rate. This study aims to compare the forward contract hedging method, money market hedging with the open position method conducted by PT. Unilever Indonesia, Tbk in an effort to reduce the risk of transaction exposure during the pandemic. The main object of this research is derivative transactions contained in the company's financial statements. This research is a descriptive research with a qualitative approach. Sources of data used are secondary data obtained from the annual financial statements of PT. Unilever Indonesia, Tbk in 2019 Quarter IV – 2020 Quarter III.